Crime In Poland – Spatial Distribution And Typology - Fałdowski, Marek (Scientific Journal of Bielsko-Biala School of Finance and Law, 2016)
A sense of security and public order in Poland is in the hands of the Department of Interior and Administration, where analyses of possibilities of occurrence of crime are carried out based mainly on the Police data. The findings are used to prevent and combat crime in a more effective way. Preventive actions are crucial in this respect e.g. development of relevant programmes and strategies, as well as tasks for units subordinated and supervised by the competent Minister of the Interior. The above mentioned effectiveness is also influenced by cooperation with institutions and organisations dealing with various aspects of crime prevention at the national and international level. While assessing crime, efficiency of the police activities as far as crime prevention and combat, statistical data including particular crime offences that determine time and place are useful. The statistics is the key element in determination of perpetrators’ actions. It is also an indicator of activities performed by individual Police units, inter alia by adequate (at place and time) services deployment (preventive and criminal ). Based on crime statistical data, one may possess knowledge of the desired Police operations, and social demands. On one hand, the analysis of statistical data related to crime and examination of the sense of security felt by Polish citizens, is one of the evaluation methods of the activities of the Polish Police forces; on the other, it offers a number of paths in the search for solutions concerning prevention and fight against crime. The indicated analyses including data interpretation are supposed to raise awareness concerning the phenomenon of crime in Poland, and demonstrate changes over years with respect to security and public order, as well as social assessment of the Police activity.